Waste marble sludge and calcined clay brick powders in conventional cement farina production for cleaner built environment - Mehmet Serkan Kırgız; Jamal Khatib; Andre Gustavo de Sousa Galdino; Said Kenai; Ahmed Ashteyat; Raul D.S.G. Campilho; Roberto Alonso Gonzalez Lezcano; Gideon Olukunle Bamigboye; N. Nagaprasad; Krishnaraj Ramaswamy (Scientific Reports)
Abstract In the manufacturing of some sectors, such as marble and brick, certain byproducts, such as sludge, powder, and pieces containing valuable chemical compounds, emerge. Some concrete plants utilize these byproducts as mineralogical additives in Turkey. The objective of the experimental study is to ascertain whether the incorporation of waste from the marble and brick industries, in powder form, into cement manufacturing as a mineralogical additive or substitute is a viable option. The materials used in this study were marble and brick wastes, CEM I 42.5 N cement, CEM I 42.5 clinker, water and CEN standard sand. as a replacement for the cement and a substitution for the clinker, the waste marble sludge powder and calcined clay brick powder was separately replaced with either CEM I 42.5 N cement or CEM I 42.5 clinker To determine the usability of marble and brick wastes in conventional cement and clinker production. To this end, there were prepared twenty-four different binder constituents at 0, 6, 10, 20, 21, and 35%. Then the hardened mortar samples were prepared with the new twenty-four different binders, standard drinkable water, and standard mortar sand. Besides, to evaluate pozzolanic activity, the construction lime was mixed with the marble and brick wastes. The microstructure of the marble and brick waste was analyzed using X-ray fluorescence, scanning electron microscopy and energy dispersive spectroscopy. In addition to the microstructure analyses, the chemical features of the marble and brick wastes, including oxides, loss on ignition, pH, total organic content and clay content, were determined in accordance with current standards. The physical and pozzolanic features of the wastes, such as their fineness, density, specific surface area, water permeability, and flexural and compressive strengths, were also evaluated using up-to-date standards. The results of the chemical experiments indicate that the total oxides of calcium, silica, alumina, and ferrite in marble powder and brick powder are more than 54% and 82%, respectively. Marble powder and brick powder are more finely ground than a few mineralogical materials, such as fly ash and silica fume, according to the residue amounts on sieves. Consequently, marble and brick powders can be used as water reducers in mortar, grout, and concrete. Moreover, marble and brick powder have a higher density than many mineralogical materials, making them suitable for applications requiring a higher binder feature of cement, higher strength, and improved durability of mortar and concrete. The specific surface area and water permeability of the marble and brick powders provide compelling evidence to support the inferences previously made about the fineness and density of these materials. Additionally, the pozzolanic properties of the brick powder were three and fourteen times greater than those of the marble powder, as evidenced by its compressive and flexural strengths, respectively. It can be reasonably deduced from the experimental results that marble powder is a latent hydraulic mineralogical natural additive or substitute, while brick powder is an unnatural mineralogical pozzolanic additive or substitute for cement-making processes.